2013
DOI: 10.1093/neuonc/not054
|View full text |Cite
|
Sign up to set email alerts
|

The soluble form of the tumor suppressor Lrig1 potently inhibits in vivo glioma growth irrespective of EGF receptor status

Abstract: BackgroundDeregulated growth factor signaling is a major driving force in the initiation and progression of glioblastoma. The tumor suppressor and stem cell marker Lrig1 is a negative regulator of the epidermal growth factor receptor (EGFR) family. Here, we addressed the therapeutic potential of the soluble form of Lrig1 (sLrig1) in glioblastoma treatment and the mechanism of sLrig1-induced growth inhibition.MethodsWith use of encapsulated cells, recombinant sLrig1 was locally delivered in orthotopic glioblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
(52 reference statements)
1
52
1
Order By: Relevance
“…Previous studies have indicated that LRIG1 was frequently decreased in gliomas (21), and the expression level of LRIG1 is significantly correlated with the malignancy of glioma (21,33). It has also been reported that upregulation of LRIG1 expression suppresses malignant glioma cell growth and induces cell apoptosis (21,(34)(35)(36), whereas downregulation of LRIG1 expression promotes the proliferation and aggressive properties of glioma cells (37,38). Furthermore, previous studies have suggested that LRIG1 is associated with the regulation of chemosensitivity of human cancer cells (39,40).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have indicated that LRIG1 was frequently decreased in gliomas (21), and the expression level of LRIG1 is significantly correlated with the malignancy of glioma (21,33). It has also been reported that upregulation of LRIG1 expression suppresses malignant glioma cell growth and induces cell apoptosis (21,(34)(35)(36), whereas downregulation of LRIG1 expression promotes the proliferation and aggressive properties of glioma cells (37,38). Furthermore, previous studies have suggested that LRIG1 is associated with the regulation of chemosensitivity of human cancer cells (39,40).…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition of EGFR signaling by LRIG1 results from the physical interaction between both proteins, which subsequently induces the recruitment of E3 ubiquitin ligases to promote lysosomal degradation of the EGFR-LRIG1 complex (Johansson et al 2013). In glioma cells, EGFR is usually overexpressed and its downstream signaling cascades are frequently activated during the development of malignancy (Ye et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Johansson et al observed an anti-proliferative effect of LRIG1, whether or not glioma cells expressed the EGFR [10]. Nor could we detect an effect of soluble, purified LRIG1-ECD, or coexpressed, full-length LRIG1 on the levels of EGFR, the phosphorylation of the EGFR kinase, or on the activation of EGFR signalling.…”
Section: Discussionmentioning
confidence: 59%
“…It contains 19 β-strands with 16 LRRs (numbered [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. There are 15 complete LRRs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], each with 23-27 residues, where 11 LRRs have the 24-residue repeat [LxxLxLxxNxLxxLxxxx(Hφ)xx(Hφ)xx, where Hφ is any hydrophobic amino acid residue]. LRR16 is only a partial repeat with a new pattern LxxLxIxSxxFx, where Ser appears to replace Asn in the consensus repeat (LxxLxLxxNxLxx).…”
Section: Crystal Structure Of Lrig1-lrr Domainmentioning
confidence: 99%
See 1 more Smart Citation